“PROGRAM INDONESIA PINTAR” IMPLEMENTATION FOR UPPER SECONDARY EDUCATION IN MOJOKERTO - Luqman Purwanto; Ellyta Eka Septycasari (DIA: Jurnal Administrasi Publik, 2022)
Education is one of the keys to success in effort to prepare quality resources for progress of the nation in the future. However, economic factor is one of the reasons for the high dropout rate in Indonesia. Therefore, the Government issued “Program Indonesia Pintar” Policy which aims to provide the widest opportunity for students from underpivilliged families to have access for education. The purpose of this study is to describe the inhibiting factors as well as the efforts made to overcome the problems of “Program Indonesia Pintar” implementation for the upper secondary education in Mojokerto. The results of this study indicate that the implementation of “Program Indonesia Pintar” at upper secondary level in Mojokerto encountered some obstacles seen from the policy implementation model of Van metter dan van Horn, namely the aspects of policy standards and objectives, policy sources, inter-organizational communication, characteristics of implementing agencies, socio-political economic conditios, executive dispositions. Then, the implementing agencies of “Program Indonesia Pintar” for upper secondary education in Mojokerto has sought various alternative solutions to deal with these obstacles.